Do changes in network structure explain why unemployment damages health? Evidence from German panel data - Krug, Gerhard; Prechsl, Sebastian (Social science & medicine, 2022)
We use German panel data and apply fixed effects regressions to test whether changes in social network size or composition explain why unemployment harms individuals’ health. We consider whether the number of weak ties, the number of strong ties, the share of relatives or the share of unemployed individuals among strong ties mediate the negative relation between unemployment and health. We look at various health and health behavior outcomes, such as self-rated health, mental health, physical health, the number of doctor visits and the number of cigarettes smoked. We find no evidence that structural features of the social network play a role in mediating the health-damaging effect of unemployment. We conduct a variety of supplementary analyses that support and extend our results, including mediation tests for emotional support and contact intensit
Keywords: unemployment; social networks; panel data; fixed effects regression; mediation; contact frequency; social support; Diversity

Reciprocity and job mobility: The effect of effort-reward imbalance in the employer-employee relationship on turnover intentions and actual job changes - Prechsl, Sebastian (Social Science Research, 2025)
Numerous studies illustrate that a lack of reciprocity between effort and reward in the employer-employee relationship produces negative effects on employees’ health and well-being. This might motivate employees to change jobs as a consequence. Based on German panel data with 16,243 observations from 4,641 employees, I analyze the effect of effort-reward imbalance (ERI) on turnover intentions and actual job changes and whether health-threatening ERI exposure affects the realization of job changes. The results indicate more frequent doctor visits, lower job satisfaction, higher turnover intentions, and higher job change probabilities when employees’ efforts in relation to rewards increase. The ERI effects on turnover intentions and job changes are both mediated through job satisfaction. Finally, I find no evidence that ERI exposure moderates the relationship between turnover intentions and actual job changes.<br
Keywords: Effort-reward imbalance Employer-employee relationship Health Job change Job satisfaction Panel data Reciprocity Turnover intentions

Shelter from the storm: do partnerships buffer the well-being costs of unemployment? - Prechsl, Sebastian; Wolbring, Tobias (European Sociological Review, 2024)
This article contributes to the existing literature on the effects of unemployment on subjective well-being (SWB) by partnership status. We argue that material and latent deprivation can explain the effects of becoming and remaining unemployed on SWB by partnership status, as both partners and their employment status crucially shape the extent of deprivation. To test our hypothesis about partnership-specific unemployment effects on SWB and the mediating roles of latent deprivation (in terms of status loss) and material deprivation, we use 14 waves of German panel data. To identify time-varying unemployment effects, we rely on time-distributed fixed effects models. Our results suggest a strong negative and rather time-constant impact of unemployment on SWB, buffered over time for those with working or nonworking partners. Furthermore, our results indicate in particular material deprivation but also latent deprivation to be relevant mechanisms for explaining partnership-specific trajectories in the loss of SWB.
Keywords: Moderation; Panel Data; Subjective Well-Being; Unemployment

“Shelter from the Storm:” Do Partnerships Buffer Well-Being Costs of Unemployment? - Prechsl, Sebastian; Wolbring, Tobias (2022)
This paper contributes to the existing literature on the effects of unemployment on subjective well-being (SWB) by partnership status. We argue that material and latent deprivation can explain effects of unemployment on SWB by partnership status, as both partners and their employment status crucially shape the extent of deprivation. To test our hypothesis about partner-specific unemployment effects on SWB and the mediating roles of latent deprivation (in terms of status loss) and of material deprivation, we use fourteen waves of German panel data. To identify time-varying unemployment effects, we rely on time-distributed fixed effects models. Our results suggest a strong negative and rather time-constant impact of unemployment on SWB, buffered over time for those with working or non-working partners. Further, our results indicate material deprivation and status loss to be relevant mechanisms for explaining partner-specific trajectories in the loss of SWB.</
Keywords: Subjective well-being; unemployment; partnership status; buffering; panel data; Gender

Social policy and labor supply: The impact of activating labor market institutions on reservation wage - Fuchs, Benjamin; Prechsl, Sebastian; Wolbring, Tobias (2021)
Activation is still an efficacious policy paradigm in modern welfare states. Taking the case of Germany, we study the relationship between the embeddedness of benefit recipients in activating labor market institutions and individual labor supply. Using panel data, we estimate the effects of transitions between key institutional states with different degrees of activation on reservation wages. We show that reservation wages react to activation: the transition from gainful employment to unemployment benefit receipt leads to an average decrease of 3.1 percent in reservation wages. The transition from gainful employment to welfare benefit receipt – an institutional state with far more rigorous activation – leads to a stronger decrease of 4.9 percent. Mediation analyses show that the income associated with different institutional states is the predominant mechanism that drives the effect on reservation wages. However, subjective social status also partly mediates the effect. Implications of these findings for active labor market policies are discussed.
Keywords: Gender

Social policy and labour supply: The impact of activating labour market institutions on reservation wages - Fuchs, Benjamin; Prechsl, Sebastian; Wolbring, Tobias (Socio-Economic Review, 2023)
Activation is an efficacious policy paradigm in modern welfare states. Taking the case of Germany, we study the relationship between the embeddedness of benefit recipients in activating labor market institutions and individual labor supply. Using panel data, we estimate the effects of transitions between key institutional states with different degrees of activation on reservation wages. We show that reservation wages react to activation: the transition from gainful employment to unemployment benefit receipt leads to an average decrease of 3.1 percent in reservation wages. The transition from gainful employment to welfare benefit receipt – an institutional state with far more rigorous activation – leads to a stronger decrease of 4.9 percent. Mediation analyses show that the income associated with different institutional states is the predominant mechanism that drives the effect on reservation wages. However, subjective social status also partly mediates the effect. Implications of these findings for active labor market policies are discussed. <
Keywords: Labor market institutions; labor supply; social policy; social security; wages; welfare state; Gender

The Intervening Role of Social Integration in the Effect of Education on Subjective Mental Health - Kroh, Jacqueline; Prechsl, Sebastian (Research in Social Stratification and Mobility, 2023)
This paper contributes to the literature examining the interplay of education, social integration, and mental health. Based on social network theories, we argue that social integration plays a role in explaining the link between education and mental health. Using data from the German Panel Study Labour Market and Social Security (PASS) (observation period: 2006/2007–2018), our sample comprises 16,870 individuals. We use panel regression models to analyze the association between education and the probability of reporting at least good mental health. Based on mediation analysis techniques, we investigate the mediating role of strong and weak ties in this relationship. Results show that overall social integration, the number of close friends and relatives, and memberships in voluntary associations partly explain the link between education and mental healt
Keywords: Mental health inequalities; education; social integration; social networks; mediation analysis; Diversity

The Intervening Role of Social Relationships in the Effect of Education on Mental Health - Kroh, Jacqueline; Prechsl, Sebastian (2022)
This paper contributes to the literature examining the interplay of education, social relationships, and mental health. Based on social network theories, we argue that the number of social relationships plays a role in explaining the link between education and mental health. Using data from the German Panel Study Labour Market and Social Security (PASS) (observation period: 2006/2007 to 2018), our sample comprises 24,450 individuals. We use random-effects panel regression models to analyze the association between education and the probability of reporting at least good mental health. Based on mediation analysis techniques, we investigate the mediating role of social relationships in this relationship. Results show that a person’s overall level of social integration, the number of close friends and relatives, and memberships in voluntary associations partly explain the effect of education on mental healt
Keywords: Mental health inequalities; education; social capital; social networks; social relationships; mediation analysis; Inklusion

The role of social integration in the adverse effect of unemployment on mental health – Testing the causal pathway and buffering hypotheses using panel data - Krug, Gerhard; Prechsl, Sebastian (Social Science Research, 2020)
Social integration is considered crucially important for understanding the adverse effect of unemployment on mental health. Social integration is assumed to either bring about the health effects of unemployment (causal pathway hypothesis) or shield the unemployed from such effects (buffering hypothesis). However, there is scarce empirical evidence, especially based on panel data, regarding these two hypotheses. In our analysis, we use up to ten waves of the “Labour Market and Social Security” (PASS) German panel study and apply fixed effects panel regressions to account for unobserved confounders. We test several indicators that cover different aspects of social integration (numbers of strong and weak ties, conflict in the household, employed friends, general and job search-specific social support). We find no empirical support for the causal pathway hypothesis and only very limited support for the buffering hypothesi
Keywords: Unemployment; Mental health; Social integration; Social support; Social networks; Moderation; Mediation; Panel data; Causal path; Buffering